Manajemen Layanan Peserta Didik Inklusif di Kota Palangka Raya - Erawati, Desi; Dian, Ana Kamerloh; Nurwidiantoro, Nurwidiantoro (Jurnal Studi Agama dan Masyarakat, 2017)
Service management becomes important to provide a good service to the learners in general, especially on learners inclusive. The focus of the issues examined is how the pattern of service management, especially learners inclusive in SMAN 4 Palangkaraya and how the factors that hinder the management services on learners inclusive, and are there any obstacles in providing services to students at SMAN 4 Palangkaraya inclusive. This study used a qualitative approach, using a sampling technique is purposive sampling.